Act in Contemporary Painting (Al-Academy, 2024)
This research concerned with studying act in contemporary painting , based on the role played by the act in achieving the structure of plastic art work artistically and aesthetically . The study consisted of three chapters: In the first one (the methodological framework) the problem has been displayed and the research aimed to detect : 1. The concept of the act in the structure of contemporary painting . 2. The impact of the act in the formation of the artistic style . as well as putting its boundaries represented in artistic movements : Abstract Expressionism , Pop Art and Conceptual Art within the period between 1945 and until the end of the seventh decade of the twentieth century. The Chapter II (theoretical framework) consisted of three sections : the first interested in the concept of the act . The second was the concept of the act in the art of painting . The third concerned with artistic Movements which are the subject of the study. The end of the Chapter was the indicators resulting from it . The third chapter included research procedures. The study found a set of results , including : 1. The concept of the act in contemporary painting to activate the visual elements in such process that achieve the launch of its effectiveness, as this activation is through the creation of relationships between these elements share the impact and vulnerability within the formal structure already achieved the same. 2. The activation of matter energies in the postmodern painting was made by the technical and performances processes , and These processes of references back to the modes of modern painting , but it has seen in the postmodern painting breaking new ground and wide by the transformation of thought , change attitudes towards the artwork.3. The act is the one who achieves the style according to the artistic and aesthetic vision of each artistic movement in the postmodern painting .